2001
DOI: 10.1159/000046614
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Chronic Myeloproliferative Diseases

Abstract: Increased angiogenic activity has been demonstrated in myelofibrosis with myeloid metaplasia (MMM), chronic myeloid leukemia (CML), and essential thrombocythemia (ET) by both bone marrow microvessel density evaluation and measurement of circulating angiogenic factors. MMM is probably the disease with the more pronounced angiogenesis among myeloproliferative disorders but the significance of this finding remains speculative since the angiogenic activity is not correlated with any of the clinical and laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 17 publications
(21 reference statements)
4
40
1
6
Order By: Relevance
“…Previous studies have demonstrated the presence of increased bone marrow angiogenesis in patients with CML. [12][13][14][15] As in the other hematological malignancies with a similar finding, increased bone marrow angiogenesis appears to have prognostic value in CML, predicting both progression and survival. 14 Malignant cells in CML may have a direct role in the formation of these new blood vessels, and studies suggest that inhibition of angiogenesis may at least in part explain the mechanism of action of drugs used in CML.…”
supporting
confidence: 59%
“…Previous studies have demonstrated the presence of increased bone marrow angiogenesis in patients with CML. [12][13][14][15] As in the other hematological malignancies with a similar finding, increased bone marrow angiogenesis appears to have prognostic value in CML, predicting both progression and survival. 14 Malignant cells in CML may have a direct role in the formation of these new blood vessels, and studies suggest that inhibition of angiogenesis may at least in part explain the mechanism of action of drugs used in CML.…”
supporting
confidence: 59%
“…Recently, the fact that angiogenesis may have an important role in hematological malignancies has attracted considerable attention and this has lead to conducting of new studies regarding the role of neovascularization in adult and pediatric acute leukemia, chronic leukemia, myelodysplastic syndromes, lymphomas and multiple myeloma (6,(13)(14)(15)(16)(17)(18)(19). Although increased angiogenesis in solid hematological tumors such as lymphomas looks reasonable in the light of the pathogenesis underlying solid tumorinduced angiogenesis, it is difficult to answer the question why tumors like acute leukemia that are liquid in nature induce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have demonstrated increased angiogenesis and angiogenic factors in acute leukemia (6,(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that ET manifests a mild increase in the number of vessels but not any severe variation from normal vascular structures (39). In addition, only a striking distention of vascular structures is noticed in PV, but not a significant increase in the number of vessels (12,39), as opposed to MF that exhibits an increased angiogenesis. Finally, although the number of patients is not high, there were clear statistical significant differences between patients with and without MF.…”
Section: Discussionmentioning
confidence: 99%